Cardiovascular Risk Factors in White Collar Workers Under Shift Work - Vangelova K. (Acta Medica Bulgarica, 2017)
Shift work is associated with circadian disruption, disturbs sleep and social life, and modifies disease risk factors, and thus can potentially contribute to various chronic diseases including cardiovascular diseases. The aim of the study was to follow cardiovascular risk in white collar workers under shift work. Cardiovascular risk was studied in sound-engineering staff in sound-recording production. The study encompassed 168 employees (46% males and 54% females) working under shift work of age 48.04 ± 8.8 years and length of service 21.6 ± 4.6 years. Our data show that 31.1% of the investigated employees were hypertensive, of which 22.6% had preliminary physician’s diagnosis of arterial hypertension, showing comparatively high rates of undiagnosed hypertension, higher in males in comparison to females. The TC and HDL-C were slightly higher with the females, while the triglycerides and TC/HDL-C ratio with the males. High rates of smoking, physical inactivity, overweight and obesity were found with both genders, slightly higher with the females. The preventive approach incorporating regular medical surveillance of shift workers and health promotion covering both life style factors and shift work organization is needed for tackling CVD in shift workers for better cardiovascular health.